Implementing control theory on Micro:bit car - Tang, Lit En (Nanyang Technological University, 2024)
This final year project examines the integration of Proportional-Integral-Derivative (PID) control theory on the BBC Micro:bit platform, highlighting its educational potential for introducing young learners to advanced control systems in an accessible manner. By focusing on the design, implementation, and optimization of PID controllers on Micro:bit-based vehicles, this study illustrates the practical application of control theory through three projects: a radio-controlled car, a line-following robot, and a conceptual line-maze solver. Each project demonstrates the adaptability of PID controllers to educational tools, enhancing learning through interactive experiments. The findings underscore the significance of PID controllers in bridging theoretical knowledge with hands-on application, fostering a deeper understanding of engineering principles among novices.